(3MjGI GdCQhGM heTcGI GdeUHGMs - (3GdMGQKj, GdYGedj, GdcaYej, EHQGgje Hf Ydj Hf GdMSf, J (B905(3g`s ((3eMeO CTQa Hf LYaQ GdQcGhjOjs)
(3ChdgG (B:s
(3GdMeO ddg MeOG(B... (3hTcQG dG jZGOQ eYQhaG(B... (3CeG HYO, aEf ef EfYGe Gddg Pj GdLdGd hGdEcQGe(B... (3hSejJg HcJGH(B: (3MjGI GdCQhGM heTcGI GdeUHGMs
(3BNQgG (B:s
(3Cbhd hHGddg GdJhajb hgh GdgGOj Edi ShGA GdWQjb(B... (3hdG JQLJ GdCfaS (B.. (3Edi HQO XdgG GdaVaGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B53s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdCOHs